The Cost of Food Safety - Annelys Hessing; Renée Goodrich Schneider; Alan Gutierrez; Rachael Silverberg; Michael S. Gutter; Keith R. Schneider (EDIS)
This new publication discusses the costs and long-term benefits associated with the implementation of food safety programs. This 5-page fact sheet covers the history of HACCP, costs associated with the application of food safety programs, reasons to improve food safety, and the financial impact of foodborne illnesses. Written by Annelys Hessing, Renée Goodrich Schneider, Alan Gutierrez, Rachael Silverberg, Michael S. Gutter, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition, October 2015.